Argentina: publicly funded science under threat - Debat, Humberto Julio (Nature Research, 2023)
Last month, Javier Milei, Argentina’s leading presidential candidate, declared his intent to shut down the Ministry of Science, Technology and Innovation and to privatize CONICET, the country’s National Scientific and Technical Research Council (see go.nature.com/3wbiurm). Such mistrust of state-funded initiatives underestimates the importance of public investment in science and technology for driving progress and economic growth.